Can young innovators save farming in the Middle East? - Rabie, Sarad; Taiwo, Ibukun (2025)
This blogpost explores the role of youth and young farmers in driving innovation, boosting climate resilience, and laying the groundwork for long-term regional stability in the MENA region.